The Influence of Teacher Competence on Student Learning Outcomes at PGRI Ciasmara Middle School, Bogor - Agus Ali; Yulia Handayani (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
This research is motivated by the low level of teacher competence in Indonesia. There is still a lack of certified teachers, there are still teachers who teach who have not completed their studies and there are still teachers who teach non-linearly (not in accordance) with their abilities. This study aims to determine the effect of teacher competence on student learning outcomes at SMP PGRI Ciasmara Bogor. The method used in this study is a quantitative with the research design is of ex-post facto. This is demonstrated by the result of this study: (1) proficiency level of teachers in SMP PGRI Ciasmara Bogor is in good category; (2) level of learning outomes of students in SMP PGRI Ciasmara Bogor is in the good category. Statistical calculations show that learning outcomes are in the good range from a cognitive and psychomotor perspective (36.0%) and the emotional learning outcomes fall into sufficient category(37.0%); (3) there is a positive influence between teacher competence on student learning outcomes at SMP PGRI Ciasmara Bogor.proven by the value of tcount > ttable, which is 3,097 > 2,602. Based on the results of these studies, it can be concluded that there is an influence of teacher competence on student learning outcomes at SMP PGRI Ciasmara Bogor.